Distribution of bulk unit weight of residual soils from the Northern Malaysia. (November 2019) - Jamalludin, D; Ahmad, A; Zakaria, Z; Hashim, M; Ibrahim, A; Ahmad, F
Abstract: A total of 284 bulk unit weight data were obtained from soil samples collected from 29 failed slopes and 10 stable slopes in Penang Island and Baling, Kedah. Both study areas are located in the Northern Malaysia. Field bulk density tests were performed at all the locations where disturbed soil samples were also collected to determine the other basic important properties of the residual soils. The highly variable values of bulk unit weight are due to the high complexity and variable formation of the residual soils. The objective of this research is to determine the best-fit distribution of the highly variable values of bulk unit weight of the soil taken from the stable slopes and failed slope especially in Northern Malaysia. This research also aims to determine the mean value of bulk unit weight of residual soils. The bulk unit weight data was tested based on Kolmogorov-Smirnov method using SPSS software, to check the normality of the data distribution. The best-fit distribution for the variation of bulk unit weight of the residual soils taken in the Northern Malaysia was normal distribution. The mean value was found to be 17.30 kN/m 3 . The range of bulk unit weight found here is within the range that was found by the earlier researchers.